Visualisasi Permainan Tradisional dalam Seni Grafis Kontemporer - Bulan Fi Sabilillah (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
Traditional games play a crucial role in children's motor, cognitive, and social development. However, changes in times and rapid technological advancements have led to a greater preference for digital games, replacing traditional games rich in cultural and philosophical values. This phenomenon occurs not only in urban areas but also in rural communities, resulting in reduced social interactions and a weakening connection between children and their cultural heritage. To preserve the existence of traditional games, contemporary art is chosen as a medium to document and reinterpret the local wisdom embedded in these games. Through high-relief printmaking using the reduction technique, this work aims to capture public attention and evoke nostalgia, inspiring younger generations to reconnect with and appreciate traditional games. The artwork is printed on fabric and displayed by hanging, offering a more dynamic visual experience compared to conventional framed artworks. With this approach, contemporary printmaking is expected to serve as an educational and reflective medium for society in rediscovering fading cultural values.